Long-term firm growth: An empirical analysis of US manufacturers 1959-2015 - Giovanni Dosi; Marco Grazzi; Daniele Moschella; Gary P. Pisano; Federico Tamagni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2019)
Firm growth is an essential feature of market economies, shaping together macroeconomic performance and the evolution of industry structures. As a potential indicator of organizational "fitness" within a competitive environment, firm growth is also a central concern to both the practice and theory of business strategy. Despite both its theoretical and practical importance, though, growth remains a poorly understood property of firms. While previous studies have documented the highly skewed nature of firm growth rates, we know far less about the persistence of growth rates over long-periods of time. For instance, do "fast growers" tend to maintain their relative growth rates advantages over long-periods or is superior growth a transitory phenomenon? Is, as predicted by evolutionary and capability based theories of the firm, the process of firm growth path-dependent or is it more akin to a random walk? The answers to these questions are central to building a robust theory of firm growth. This paper attempts to address this gap in our empirical knowledge of firm growth using a dataset that spans 50 years, which allows the abandonment of the assumption, common to all incumbent studies, that the stochastic paths of all firms stem from the same generating process. These exploratory results indicate that growth rate persistence is there and my be even substantial for some firms, but it is rare. We also study the links between the micro- properties of firm growth within sectors and the patterns of aggregate growth of these same sectors. Indeed, we find circumstantial but widespread evidence that heterogeneity across firms correlates with industry dynamism.
Keywords: C81; D21; D22; D24; L11; L21; L25; L62; L63; 330; Firm growth; Persistence; Industrial Dynamics; Firm heterogeneity